Respuesta :
Answer:
- [tex]x+\cfrac{1}{x} =7[/tex]
================
Given:
- [tex]x^2+\cfrac{1}{x^2} =47[/tex]
Add 2 to both sides of equation:
- [tex]x^2+\cfrac{1}{x^2}+2 =47+2[/tex]
Then follow the steps:
- [tex]x^2+\cfrac{1}{x^2}+2*x*\cfrac{1}{x} =49[/tex]
- [tex](x+\cfrac{1}{x})^2=7^2[/tex]
Take square root of both sides to get:
- [tex]x+\cfrac{1}{x} =\pm\ 7[/tex]
We are taking the positive value as we are told x > 0, hence the answer is 7.
[tex] \qquad \qquad \bf \huge\star \: \: \large{ \underline{Answer} } \huge \: \: \star[/tex]
- x + 1/x = 7
[tex]\textsf{ \underline{\underline{Steps to solve the problem} }:}[/tex]
[tex] \qquad❖ \: \sf \: {x}^{2} + \cfrac{1}{ {x}^{2} } = 47[/tex]
[tex] \qquad❖ \: \sf \: {x}^{2} + \cfrac{1}{ {x}^{2} } + 2 - 2 = 47[/tex]
( adding and subtracting 2, doesn't change the value )
[tex] \qquad❖ \: \sf \: {x}^{2} + \cfrac{1}{ {x}^{2} } + 2 = 47 + 2[/tex]
[tex] \qquad❖ \: \sf \: {x}^{2} + \cfrac{1}{ {x}^{2} } + \bigg(2 \sdot x \sdot \cfrac{1}{x} \bigg) = 49[/tex]
( x cancel out, so no change in value )
[tex] \qquad❖ \: \sf \: \bigg(x + \cfrac{1}{x} \bigg) {}^{2} = 49[/tex]
( use identity a² + 2ab + b² = (a + b)² )
[tex] \qquad❖ \: \sf \: \bigg(x + \cfrac{1}{x} \bigg) {}^{} = \sqrt{49} [/tex]
[tex] \qquad❖ \: \sf \: x + \cfrac{1}{x} {}^{} = \pm7[/tex]
since we have to take positive value, i.e greater than 0
[tex] \qquad❖ \: \sf \: x + \cfrac{1}{x} {}^{} = 7[/tex]
[tex] \qquad \large \sf {Conclusion} : [/tex]
Therefore, the required value is 7